Almost and Strongly Almost Approximately Nearly Quasi Compactly Packed Modules - Ajeel, Ali Sh.; Mohammadali, Haibat K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this paper, we present the almost approximately nearly quasi compactly packed (submodules) modules as an application of the almost approximately nearly quasiprime submodule. We give some examples, remarks, and properties of this concept. Also, as the strong form of this concept, we introduce the strongly, almost approximately nearly quasi compactly packed (submodules) modules. Moreover, we present the definitions of almost approximately nearly quasiprime radical submodules and almost approximately nearly quasiprime radical submodules and give some basic properties of these concepts that will be needed in section four of this research. We study these two concepts extensively.